The Study of Electrical Conductance Spectroscopy of The Inner membrane of Salak - Wenny Maulina (UPT Penerbitan Universitas Jember, 2016)
Main objective of the present work was to investigate mechanism transport of the inner membrane of salak (Salacca edulis) using electrical conductance measurements. The inner thin membrane obtain after removing the outer cover of salak has been found to record electrical conductance when it separates two different concentration of electrolyte solution; NaCl, MgCl2 and CaCO3. Conductance values were measured for each concentration at different temperature. The temperature range studied is between 303 K and 333 K at 5 K intervals. The normal behaviour of these conductance shows that the values increase smoothly with increase in concentration. The magnitude follow the order Mg2+ > Na+ > Ca2+. The increase of temperature makes mobilisation of the ions was rapidly during the measurement of conductance.